(untitled) (Historia, 2021)
Afrikaans Vir die Portugese was Ilha de MoÁambique [Mosambiek-eiland] vanaf die begin van die sestiende eeu die belangrikste aandoeningspunt op die Carreira da Índia, die heen- en terugvaart tussen Portugal en IndiÎ. Nadat die Vereenigde Oost-Indische Compagnie (VOC) in 1602 gestig is, het die Nederlanders met begerige oÎ na diÈ strategiese eiland gekyk. By drie geleenthede, naamlik in 1604, 1607 en 1608, het hulle onsuksesvolle pogings aangewend om die Portugese vesting op die eiland, die Fortaleza de São Sebastião, deur blokkades te verower. Vooraanstaande historici soos C.R. Boxer, W.Ph. Coolhaas, J.M. Garcia en veral Eric Axelson wys daarop dat die geskiedenis van Suider-Afrika ŉ totaal ander loop sou geneem het indien die Nederlanders wel Ilha de MoÁambique verower het. Volgens hulle kan die stigting van die Nederlandse verversingspos aan die Kaap die Goeie Hoop in 1652 onder meer aan hierdie mislukte blokkades toegeskryf word. In algemene Suid-Afrikaanse geskiedenisboeke word hierdie betekenisvolle botsings tussen die Portugese en die Nederlanders aan die ooskus van Afrika met hulle verreikende gevolge egter verswyg of skaars vermeld. English How Ilha de Moçambique almost became Dutch – instead of the Cape of Good Hope From the beginning of the sixteenth century, Ilha de MoÁambique [Mozambique Island] represented for the Portuguese the most important port of call in the Carreira da Índia, the round voyage between Portugal and India. After the Dutch East India Company (DEIC) had been founded in 1602, the Dutch cast longing eyes at this strategic island. On three occations ñ in 1604, 1607 and 1608 ñ they made unsuccesful efforts, by means of blockades, to capture the fortress on the island, the Fortaleza de São Sebastião. Prominent historians like C.R. Boxer, W.Ph. Coolhaas, J.M. Garcia and especially Eric Axelson emphasise that the history of Southern Africa would have taken an altogether different direction, had the Dutch indeed succeeded in capturing Ilha de MoÁambique. According to them, the fruitless blockades of the island had been one of the reasons why the Dutch eventually established their refreshment station at the Cape of Good Hope in 1652. However, in general South African history books, these significant and far-reaching clashes between the Portuguese and Dutch on the east coast of Africa are rarely, if ever, mentioned.